2022
DOI: 10.3389/fpubh.2022.956711
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up management service and health outcomes of hypertensive patients in China: A cross-sectional analysis from the national health service survey in Jiangsu province

Abstract: BackgroundHypertension is a major cause of early mortality worldwide. Health follow-up management services can encourage patients with hypertension to improve their health behavior and outcomes. However, a lack of studies on the relationship between specific factors of follow-up management and both subjective and objective health outcome among hypertensive patients exists. The current study investigated the relationship between service content, frequency, mode, and institutions of follow-up management and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…It may be related to the fact that the BPHS system in Yunnan Province has linked multiple medical electronic databases, benefiting from the management of more patients. Such patients receiving more BPHS accessible health education services, a better awareness of their health, and improved medication adherence, similar to the study in Zhejiang Province and Jiangsu Province in China (25,47). Moreover, 17.3% of the BPHS patients used a combination of antihypertension drugs (vs. non-BPHS 8.6%), which has facilitated blood pressure control to normal in patients in the BPHS group.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It may be related to the fact that the BPHS system in Yunnan Province has linked multiple medical electronic databases, benefiting from the management of more patients. Such patients receiving more BPHS accessible health education services, a better awareness of their health, and improved medication adherence, similar to the study in Zhejiang Province and Jiangsu Province in China (25,47). Moreover, 17.3% of the BPHS patients used a combination of antihypertension drugs (vs. non-BPHS 8.6%), which has facilitated blood pressure control to normal in patients in the BPHS group.…”
Section: Discussionsupporting
confidence: 81%
“…With BPHS, 35.1% of hypertensive patients have received four or more follow-up assessments in the past 1 year ( 19 ), uncontrolled hypertension was reduced by 26% ( 20 ). However, most of the earlier studies on being covered by BPHS were self-reported by participants, and focused on the rate of service delivery from primary doctors ( 21 , 22 ), patient service satisfaction ( 23 , 24 ) and the community health management rate of hypertensive patients ( 25 , 26 ). Previous studies also showed a low prevalence of combination therapy and limited compliance with hypertension drug treatment ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adequate follow-up was significantly associated with control status among adults with hypertension, with an odds ratio of 2.34. Peng et al [ 21 ] conducted a study among the Chinese population and reported similar results. Regular follow-up will not only increase awareness but also increase adherence and compliance to medication among adults [ 22 - 24 ].…”
Section: Discussionmentioning
confidence: 69%
“…Studies have shown that hypertension can be prevented and improved through effective management [ 17 ]. Follow-up visits of hypertension are regular clinic activities for hypertensive patients to achieve blood pressure control, emphasized by a series of hypertension guidelines [ 18 ]. Regular follow-up visits of hypertension could enhance blood pressure monitoring and improve medication adherence, thereby preventing complications and reducing medical expenses [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, patients with hypertension may be diagnosed and initially followed up in large hospitals and clinics, considered to be "passive" health management for disease causes [ 21 ]. Further, a high frequency of follow-up services improved the health level and health awareness of hypertensive patients leading residents proactively to seek health management and sign with family doctors [ 22 , 23 ]. Primary health workers have also contributed greatly to increasing family doctor contracting rates for patients with hypertension follow-up management [ 13 , 24 ].…”
Section: Introductionmentioning
confidence: 99%